Analisis Kinerja PT. Amanah Insanillahia Batusangkar dengan Metode Balancescorecard - Mega Rahmi; Febby Tiara Revinda (JURNAL PUNDI, 2020)
This study analyzes the performance of PT. Amanah Insanillahia uses the balace scorcard method from a financial, customer, internal business process, and learning and growth perspective. Financial perspective is measured using profitability ratios, growth ratios, and shareholder value. Customer perspective is measured using the Core Measurement Group and Customer Value Proposition. The internal business process perspective is measured by the innovation process, the operating process and after-sales service. Learning and growth perspectives are measured by employee satisfaction, worker retention and worker productivity. Viewed from a financial perspective, PT. Amanah Insanillahia Batusangkar financial ratio measurement is quite well categorized. Performance from the customer's perspective is very good. Seen from customer satisfaction indicators that customers are very satisfied with the services provided by the company. Seen from the perspective of internal business processes it is said to be good, because PT. Amanah Insanillahia Batusangkar is able to increase sales of its products and always try to maintain consumer confidence by always delivering orders on time and in accordance with customer demand. Learning and growth perspective performance is categorized as good. Keywords : Balance Scorecard